2021
DOI: 10.1101/2021.10.15.21264137
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 is associated with higher risk of venous thrombosis, but not arterial thrombosis, compared with influenza: Insights from a large US cohort

Abstract: Introduction Infection with SARS-CoV-2 is typically compared with influenza to contextualize its health risks. SARS-CoV-2 has been linked with coagulation disturbances including arterial thrombosis, leading to considerable interest in antithrombotic therapy for Coronavirus Disease 2019 (COVID-19). However, the independent thromboembolic risk of SARS-CoV-2 infection compared with influenza remains incompletely understood. We evaluated the adjusted risks of thromboembolic events after a diagnosis of COVID-19 co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Importantly, as exclusion criterion, in our series there were no macroscopic evidence of peripheral thrombosis, thus, this further supports the in situ formation of the arterial thrombi we found. Anyway, in a large retrospective US cohort, the risk of arterial thrombosis in COVID-19 was not higher than that reported in influenza [47] , even if this comparison is still controversial.…”
Section: Discussionmentioning
confidence: 69%
“…Importantly, as exclusion criterion, in our series there were no macroscopic evidence of peripheral thrombosis, thus, this further supports the in situ formation of the arterial thrombi we found. Anyway, in a large retrospective US cohort, the risk of arterial thrombosis in COVID-19 was not higher than that reported in influenza [47] , even if this comparison is still controversial.…”
Section: Discussionmentioning
confidence: 69%
“…In a retrospective cohort, the unadjusted incidence of ATE (AIS + AMI) was more than double in COVID-19 than in influenza (7.1 vs. 3.0%). 48 However, after propensity score matching there was no difference between the two groups (hazard ratio 1.02, 95% CI, 0.95–1.10). 48 Nemetski et al found a slightly higher incidence of ATE in patients with COVID-19 ( n = 4,451) when compared with patients hospitalized for influenza ( n = 468) or non-COVID-19 illness ( n = 40,359) and, notably, none of the influenza patients experienced an ATE.…”
Section: Discussionmentioning
confidence: 97%
“…48 However, after propensity score matching there was no difference between the two groups (hazard ratio 1.02, 95% CI, 0.95–1.10). 48 Nemetski et al found a slightly higher incidence of ATE in patients with COVID-19 ( n = 4,451) when compared with patients hospitalized for influenza ( n = 468) or non-COVID-19 illness ( n = 40,359) and, notably, none of the influenza patients experienced an ATE. 32 However, the study was retrospective and the real incidence of ATE in the non-COVID-19 population could have been underestimated.…”
Section: Discussionmentioning
confidence: 97%
“…The endothelial dysfunction should explain why individuals with COVID-19 are at high risk for venous and arterial thrombotic events [150], particularly the patients with a severe course of disease [151]. The risk is visible when comparing critically ill patients with COVID-19 and non-COVID-19 respiratory diseases [152].…”
Section: Covid-19 and The Risk Of Thrombotic Events: The Potential Ro...mentioning
confidence: 99%